Intermediate uveitis in a child with phosphatase and tensin homolog gene mutation and Bannayan-Riley-Ruvalcaba syndrome. Issue 2 (12th February 2019) - Prat, Daphna; Ben Bassat Mizrachi, Iris; Vishnevskia-Dai, Vicktoria
Abstract : Bannayan-Riley-Ruvalcaba syndrome (BRRS) is a congenital disorder characterised by macrocephaly, multiple hamartomas, lipomas, and pigmented macules of the glans penis. Intermediate uveitis is characterised by chronic inflammatory cells aggregates on the pars plana (snowbanks) and within the vitreous cavity (snowballs). We describe what we believe to be the first case of intermediate uveitis associated with BRRS. Early examination under anaesthesia should be considered in the management of young children diagnosed with this syndrome in order to provide appropriate ocular evaluation, treatment and follow-up. Further research is needed to establish a better understanding of the ophthalmic manifestations of this syndrome.